Identification of a novel lineage of Crimean–Congo haemorrhagic fever virus in dromedary camels, United Arab Emirates. (24th February 2021) - Khalafalla, Abdelmalik I.; Li, Yan; Uehara, Anna; Hussein, Nasareldien A.; Zhang, Jing; Tao, Ying; Bergeron, Eric; Ibrahim, Ibrahim H.; Al Hosani, Mohamed A.; Yusof, Mohd F.; Alhammadi, Zulaikha M.; Alyammahi, Saeed M.; et al.
Abstract : Crimean–Congo haemorrhagic fever virus (CCHFV) is a tick-borne virus causing Crimean–Congo haemorrhagic fever (CCHF), a disease reported to have a high fatality rate in numerous countries. The virus is geographically widespread due to its vector, and numerous wild and domestic animals can develop asymptomatic infection. Serological and limited molecular evidence of CCHFV has previously been reported in Camelus dromedarius (the dromedary, or one-humped camel) in the United Arab Emirates (UAE). In this study, 238 camel samples were screened for CCHFV RNA where 16 camel samples were positive for CCHFV by RT-PCR. Analysis of full-length CCHFV genome sequences revealed a novel lineage in camels from the UAE, and potential reassortment of the M segment of the genome.